Outcomes of Primary Peritoneal Drainage and Taylor’s Conservative Method in High-Risk Cases of Perforated Peritonitis - Ayra Suleman, Umbreen Anwer, Syed Asghar Naqi, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the outcomes of primary peritoneal drainage and Taylor’s conservative method in high-risk patients of perforated peritonitis. Methods: The study was carried out within 6 months after the approval of synopsis i.e. from 21st August, 2020 till 20th February, 2021, in the East Surgical department, Mayo hospital Lahore. A total of 66 patients who fulfilled the inclusion criteria were enrolled. Percutaneous peritoneal drainage was performed under local anesthesia and two wide bored intra-abdominal tube drains were placed in both flanks through these incisions. Pus/fluid/bile was evacuated. Outcomes were monitored in terms of mortality, morbidity (SSI, wound dehiscence) and need for definitive surgery after PPD within 14 days (as per operational definition). Post stratification Chi square test was applied and a p-value of ≤0.05 was considered as significant. Results: The mean age of the patients was 49±9.9. Mortality occurred in 65.2% patients, morbidity was seen in 25.8% patients, out of which 13.6% patients had superficial SSI. 62.1% patients had to undergo laparotomy. However, only 31.8% of the patients died postoperatively after definitive laparotomy, which is less than the high mortality rate in high-risk patients of perforation peritonitis. Conclusion: We have concluded from our study that PPD with Taylor’s conservative method served as an effective method of initial resuscitation and stablilization in high-risk patients of perforation peritonitis. Once the general condition of the patients improved, they were subjected to definitive laparotomy under general anesthesia. Post-laparotomy outcomes were improved in such patients. Keywords: peritonitis, drainage, laparotomy